PIMS – eine neue pädiatrische Herausforderung: 9-Jahre alter Knabe mit SARS-CoV-2 assoziiertem hyperinflammatorischem Schocksyndrom - Samueli, S. (Monatsschr Kinderheilkd, 2021)
The boy of Egyptian origin was previously healthy. After a history of fever for 7 days, abdominal pain, vomiting and dry cough resistant to treatment with oral antibiotics, he was admitted to hospital. The clinical examination showed a slightly red throat, a tense abdomen and erythema. The blood tests revealed leukocytosis and significantly increased inflammatory parameters. The abdominal ultrasound showed thickened intestinal loops in the left lower abdomen and the echocardiography showed minimal mitral regurgitation, a narrow pericardial effusion lamella over both ventricles and normal coronary arteries. Accordingly, cardiac enzymes were elevated. The day after admission, the boy developed an increasing rash and was transferred to the PICU because of septic shock refractory to high volume resuscitation, requiring hemodynamic support with noradrenaline and noninvasive respiratory assistance. The initial testing for SARS-CoV‑2 on nasopharyngeal aspirates was negative twice; however, serum IgG antibodies were positive. Other viral and bacterial infections were excluded as the cause of the symptoms. The patient received IVIG, ASS, furosemide and methylprednisolone and the antibiotic treatment was continued. The dosage of the catecholamine could be reduced according to the patient’s condition and the serially performed echocardiographic findings. The patient recovered in his general condition and was discharged from the PICU after 8 days. With the help of a detailed family history, we were able to figure out that the whole family, including the patient himself, had symptoms of a cold about 1 month earlier. Hence, SARS-CoV‑2 antibody tests carried out showed a positive result for all of them. Pediatric inflammatory multisystem syndrome (PIMS) can quickly lead to manifest shock symptoms, necessitating close monitoring. A PICU background is crucial to treat possibly occurring symptoms and complications. High-dose steroids are used therapeutically alongside supportive therapies.